PENGARUH HYPNOPREGNANCY TERHADAP TINGKAT KECEMASAN IBU HAMIL DI KLINIK "RAHSKA MOM BABY CARE" PEKANBARU - Lexi, Sri Agnes; Susanti, Revita; Afriani, Riska; Richa Rahmana, Fatma (Jurnal Penelitian Keperawatan Kontemporer, 2025)
Background: Pregnancy brings physical and psychological changes, therefore pregnant women need a conducive physical and psychological condition so that the pregnancy process until delivery can run smoothly. Physiological changes that may appear in pregnant women can be a factor in the formation of psychological problems in pregnant women, such as anxiety that arises in each trimester of pregnancy. Aim: To identify the influence of hypnopregnancy on the anxiety levels of pregnant women at Rahska mom baby care Method: This study uses a Pre-experimental research design with One Group Pre Test- Post Test Design on 23 pregnant women in the second and third trimesters. The statistical test in this study uses the Wilcoxon Signes Rank Test. Results: The statistical results using the Wilcoxon Signes Rank Test on 23 pregnant women obtained a P.Value of 0.000 ˂ 0.005. This shows that there is a significant influence between hypnopregnancy on the level of anxiety of pregnant women in the second and third trimesters preparing for childbirth. Results: The results of the Pearson correlation test with a level of error (α) = 0.05, obtained p value = 0.011. This means that there is a significant relationship between workload and caring behavior applied by nurses. Conclusion: Based on the results of this study, hypnopregnancy has an effect on the anxiety levels of pregnant women. Therefore, it is recommended that pregnant women practice hypnopregnancy regularly to reduce anxiety levels during pregnancy